Aqueous geochemistry in icy world interiors: Equilibrium fluid, rock, and gas compositions, and fate of antifreezes and radionuclides. (1st September 2017) - Neveu, Marc; Desch, Steven J.; Castillo-Rogez, Julie C.
Abstract: The geophysical evolution of many icy moons and dwarf planets seems to have provided opportunities for interaction between liquid water and rock (silicate and organic solids). Here, we explore two ways by which water-rock interaction can feed back on geophysical evolution: the production or consumption of antifreeze compounds, which affect the persistence and abundance of cold liquid; and the potential leaching into the fluid of lithophile radionuclides, affecting the distribution of a long-term heat source. We compile, validate, and use a numerical model, implemented with the PHREEQC code, of the interaction of chondritic rock with pure water and with C, N, S-bearing cometary fluid, thought to be the materials initially accreted by icy worlds, and describe the resulting equilibrium fluid and rock assemblages at temperatures, pressures, and water-to-rock ratios of 0–200 ° C, 1–1000 bar, and 0.1–10 by mass, respectively. Our findings suggest that water-rock interaction can strongly alter the nature and amount of antifreezes, resulting in solutions rich in reduced nitrogen and carbon, and sometimes dissolved H2, with additional sodium, calcium, chlorine, and/or oxidized carbon. Such fluids can remain partially liquid down to 176 K if NH3 is present. The prominence of Cl in solution seems to hinge on its primordial supply in ices, which is unconstrained by the meteoritical record. Equilibrium assemblages, rich in serpentine and saponite clays, retain thorium and uranium radionuclides unless U-Cl or U-HCO3 complexing, which was not modeled, significantly enhances U solubility. However, the radionuclide 40 K can be leached at high water:rock ratio and/or low temperature at which K is exchanged with ammonium in minerals. We recommend the inclusion of these effects in future models of the geophysical evolution of ocean-bearing icy worlds. Our simulation products match observations of chloride salts on Europa and Enceladus; CI chondrites mineralogies; the observation of serpentines, NH4 -phyllosilicates, and carbonates on Ceres' surface; and of Na and NH4 -carbonate and chloride in Ceres' bright spots. They also match results from previous modeling studies with similar assumptions, and systematically expand these results to heretofore unexplored physico-chemical conditions. This work involved the compilation and careful validation of a comprehensive PHREEQC database, which combines the advantages of the default databases phreeqc.dat (carefully vetted data, molar volumes) and llnl.dat (large diversity of species), and should be of broad use to anyone seeking to model aqueous geochemistry at pressures that differ from 1 bar with PHREEQC .